2022
DOI: 10.1177/00472395221132582
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Integration in Social Studies Classroom: Impact on Student Knowledge, Classroom Engagement, and Historical Empathy Development

Abstract: While virtual reality (VR) technology can provide students with first-hand and situational learning experiences, limited studies have integrated VR in a K-12 classroom, resulting in the lack of understanding of the benefits and challenges of VR use in classroom settings. To examine the impact of VR on student learning, this study employed a mixed-methods quasi-experimental research approach and integrated a fully immersive VR (i.e., Oculus Quest) and non-immersive VR (i.e., 3D website) into 9th-grade social st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The high degree of enjoyment expressed by participants aligns also with the Self-Determination Theory, which posits that intrinsically motivated activities that satisfy needs for competence, autonomy, and relatedness are more likely to persist across time [64]. Importantly, the positive student perceptions echo broader trends in educational technology research, where VR is increasingly recognised for its potential to enhance motivation, engagement, and overall learning satisfaction [29].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The high degree of enjoyment expressed by participants aligns also with the Self-Determination Theory, which posits that intrinsically motivated activities that satisfy needs for competence, autonomy, and relatedness are more likely to persist across time [64]. Importantly, the positive student perceptions echo broader trends in educational technology research, where VR is increasingly recognised for its potential to enhance motivation, engagement, and overall learning satisfaction [29].…”
Section: Discussionmentioning
confidence: 55%
“…The authors in [28] Marto catalogued a range of applications from virtual tours to educational games, underlining the multifaceted advantages of Virtual/Augmented Reality in the cultural heritage sector. Other researchers [19,29] have leveraged VR to animate historical settings as a means of providing a firsthand understanding of diverse cultures. Moving beyond historical perspectives, recent works [30][31][32] have demonstrated that VR's applicability is broad-extending to contemporary cultural contexts-including interactive museum exhibitions and storytelling about indigenous cultures as well as the illumination of specific cultural practices.…”
Section: Virtual Reality In Cultural Educationmentioning
confidence: 99%
“…However, qualitative data indicated positive learning benefits and increased classroom engagement. Notably, the improvement was observed to have developed due to historical empathy through VR [50]. In recent times, the implementation of AR/VR has been extended to K-12 teachers for their professional development programs.…”
Section: Ar/vr For K-12 Educationmentioning
confidence: 99%
“…Although the Peruvian government has approved the gradual return to face-to-face classes in universities, some higher education experts argue that the virtual or blended modality may continue to be offered at universities in the coming years (Navarro, López, & Caycho, 2021). However, the necessary learning outcomes cannot be ensured by online learning alone (Lu, Yang, Wu, & Yang, 2023;Riner, Hur, & Kohlmeier, 2022). The adaptability of online learning has been a challenge for universities due to the low levels of digital skills of teachers and students (Bonilla-Guachamín, 2020).…”
Section: Introductionmentioning
confidence: 99%